Studies on bagasse and its possible uses in the plastics industry - Rondain, Naomi T.; Gomez, Lilly K.; Tenmatay, Augusto L. (Quezon City Department of Chemistry, College of Liberal Arts, University of the Philippines Diliman, 1952)
Studies were made on bagasse to determine its possibility as a source of raw material for plastic manufacture. Experiments were made using bagasse pulp as filler for a synthetic resin and as a source of cellulose for the preparation of cellulose acetate; hydrolyzed bagasse was used in the preparation of lingo-cellulose plastics.
Thesis (Bachelor of Science in Chemistry)--University of the Philippines Diliman, April 1952.
Keywords: Bagasse; Sugarcane